Metabolomic Profile of Skeletal Muscle and Its Change Under a Mixed-Mode Exercise Intervention in Progressively Dysglycemic Subjects - Szczerbinski, Lukasz; Golonko, Aleksandra; Taylor, Mark; Puchta, Urszula; Konopka, Paulina; Paszko, Adam; Citko, Anna; Szczerbinski, Karol; Gorska, Maria; Zabielski, Piotr; Błachnio-Zabielska, Agnieszka; Larsen, Steen; et al. (Frontiers in Endocrinology, 2021)
Skeletal muscles play an essential role in whole-body glucose homeostasis. They are a key organ system engaged in the development of insulin resistance, and also a crucial tissue mediating the beneficial metabolic effects of physical activity. However, molecular mechanisms underlying both these processes in skeletal muscle remain unclear. The aim of our study was to compare metabolomic profiles in skeletal muscle of patients at different stages of dysglycemia, from normoglycemia through prediabetes to T2D, and its changes under a mixed-mode (strength and endurance) exercise intervention. We performed targeted metabolomics comprising several major metabolite classes, including amino acids, biogenic amines and lipid subgroups in skeletal muscles of male patients. Dysglycemic groups differed significantly at baseline in lysophosphatidylcholines, phosphatidylcholines, sphingomyelins, glutamine, ornithine, and carnosine. Following the exercise intervention, we detected significant changes in lipids and metabolites related to lipid metabolism, including in ceramides and acylcarnitines. With their larger and more significant change over the intervention and among dysglycemic groups, these findings suggest that lipid species may play a predominant role in both the pathogenesis of type 2 diabetes and its protection by exercise. Simultaneously, we demonstrated that amino acid metabolism, especially glutamate dysregulation, is correlated to the development of insulin resistance and parallels disturbances in lipid metabolites.